2021
DOI: 10.3390/rs13061076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing a Regional Territorial Evapotranspiration Dataset for Northern China

Abstract: As a vital role in the processes of the energy balance and hydrological cycles, actual evapotranspiration (ET) is relevant to many agricultural, ecological and water resource management studies. The available global or regional ET products provide ET estimations with various temporal ranges, spatial resolutions and calculation methods (algorithms, inputs and parameterization, etc.), leading to varying degrees of introduced uncertainty. Northern China is the main agriculturally productive region supporting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 88 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the ET process is complex, which is why monitoring the spatiotemporal variation in surface ET remains difficult. RS ET products are vital data sources for studying the spatiotemporal variation in ET on regional scales, such as GRACE [9,51], SSEBop [52,53], GLEAM [10,52], LSA-SAF [54,55], BESS [50,56], ETWatch [9,57], ETMonitor [9,58], etc. However, data sources vary in resolution and quality, and the assessments of ET variation are different.…”
Section: Limitations and Future Research Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the ET process is complex, which is why monitoring the spatiotemporal variation in surface ET remains difficult. RS ET products are vital data sources for studying the spatiotemporal variation in ET on regional scales, such as GRACE [9,51], SSEBop [52,53], GLEAM [10,52], LSA-SAF [54,55], BESS [50,56], ETWatch [9,57], ETMonitor [9,58], etc. However, data sources vary in resolution and quality, and the assessments of ET variation are different.…”
Section: Limitations and Future Research Directionmentioning
confidence: 99%
“…Cheng et al investigated the spatiotemporal ET patterns in China [5]. The MOD16 ET product has also been used to analyze the trend of ET variation in northwestern Mexico [6], Bulgaria [7], Mongolia [8], China [5,[9][10][11], Henan Province [12], Guizhou Province [13], Shanxi Province [14], Xinjiang [15], Yinchuan Plain [16] and Sanjiang Plain [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the calibrated parameters are often fixed as spatial and temporal constants during the application of CR models in an ungauged basin. Besides, it is generally accepted that accuracy increases as the number of adjustable parameters increases (Brutsaert, 2015; Wang et al., 2021). To improve estimation accuracy, two parameters of CR models are often calibrated simultaneously, but the risks of unreasonable spatial distribution may increase concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al [30] compared the accuracy of eight ET products (including MOD16, PML-V2 and BESS) in the Yellow River Basin and found that the Simplified Surface Energy Balance (SSEBop) model, after regional optimization, is most consistent with water balance evapotranspiration. MDO16 and SEBbased ET products were found to record a poor performance at the Murray-Darling Basin and in Northern China compared with global scales [37,38]. Therefore, the inconsistent performances of global actual ET products necessitate a comprehensive assessment before being applied at local or regional scales.…”
Section: Introductionmentioning
confidence: 99%